GUEST BOOKS AS A REFLECTION OF HOSPITALITY: THE CASE OF THE ASTORIA HOTEL AND BLED CASTLE RESTAURANT - Grafenauer, Boža (The Business of Tourism, 2025)
Guest Books as a Reflection of Hospitality: The Case of the Astoria Hotel and Bled Castle Restaurant Abstract  This paper is an analysis of guest books of the Astoria Hotel in Bled and the Bled Castle Restaurant as an important source for understanding hospitality and hotel culture. Guest books, as a historical source, offer a comprehensive approach to studying the history of travel, cultural interactions, and the hotel industry. They provide an insight into various aspects of hotel life and culture from the perspectives of both guests and employees.  The paper includes an analysis of five guest books, which contain a total of 685 entries, chronologically from 1995 to 2016. The main research question is what the guest book entries reveal about hospitality in different time periods and which elements of hospitality are highlighted. Based on the findings, the author wonders how to use or enrich the hospitality practices of the past to enhance the tourism offer/hospitality of the Astoria Hotel today. Key words: Guest book,  Astoria Hotel, hospitality,  tourism, Bled, Slovenia
Keywords: Guest book, Astoria Hotel, hospitality, tourism, Bled, Slovenia